Analisis Determinan Keberhasilan Implementasi SPBE di Pemerintah Daerah: Pendekatan Structural Equation Modeling (SEM) - Prasetyo, Restu (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2025)
This study aims to measure the significant influence of civil servants’ digital competence, ICT infrastructure, and digital leadership on the successful implementation of the Electronic-Based Government System (SPBE) in local governments. The research focuses on analyzing the determinants of SPBE success using the theoretical frameworks of the Technology-Organization-Environment (TOE) and Technology Acceptance Model (TAM). Data were collected through structured questionnaires administered to 420 civil servants across 35 local governments and analyzed quantitatively using Structural Equation Modeling (SEM). The results indicate that digital competence (β=0.28), ICT infrastructure (β=0.35), and digital leadership (β=0.31) have significant effects on SPBE implementation success. Budget allocation serves as a strengthening moderator of competence, while regulation remains ineffective. The novelty of this study lies in integrating the TOE and TAM frameworks simultaneously within the regional SPBE context in Indonesia, as well as incorporating budget and regulation as moderating variables that have received limited attention in previous research. The findings highlight the importance of synergy among civil servants’ digital competence, adequate ICT infrastructure, and digital leadership in enhancing the success of electronic-based bureaucratic transformation.